2017
DOI: 10.1007/s00213-017-4602-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural connectivity changes in betel-quid chewers using generalized q-sampling MRI

Abstract: Our results provided further evidence indicating that BQ chewing may lead to brain structure and connectivity changes in BQ chewers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Increased functional connectivity in the frontotemporal, bilateral frontoparietal, and occipital/parietal networks in BQ chewers were also found in this study. These results are similar to other recent findings ( 16 ) showing increased diffusion anisotropy in the temporal gyrus, the bilateral superior and inferior parietal lobule, and occipital gyrus. The temporal gyrus may be involved in auditory processing ( 47 ), perception of facial emotions ( 48 ), and social cognition ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Increased functional connectivity in the frontotemporal, bilateral frontoparietal, and occipital/parietal networks in BQ chewers were also found in this study. These results are similar to other recent findings ( 16 ) showing increased diffusion anisotropy in the temporal gyrus, the bilateral superior and inferior parietal lobule, and occipital gyrus. The temporal gyrus may be involved in auditory processing ( 47 ), perception of facial emotions ( 48 ), and social cognition ( 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…Decreased functional connectivity was also found in the parietal network in BQ chewers compared to HCs. Weng et al ( 16 ) found increased diffusion anisotropy in the inferior parietal lobule in BQ chewers. However, decreased long-range functional connectivity density in the bilateral inferior parietal lobule was observed in BQ chewers relative to HCs ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is little evidence examining white matter microstructure alternation in BQD individuals. A recent study using generalized q-sampling imaging reported increased diffusion anisotropy in ACC, parietal, temporal, and occipital regions in BQ chewers compared with healthy controls ( 12 ), which indicated that the influence of BQ chewing on the brain white matter. However, relatively small sample size of this study prevented us from drawing solid conclusion on white matter integrity alternation in BQ chewers.…”
Section: Introductionmentioning
confidence: 97%
“…Studies also suggested that there were decreased cognitive functions after long-term BQ chewing, such as attention and inhibition control ( 10 ). Recently, neuroimaging studies compared frequent BQ chewers and controls and found that frequent chewers have altered brain structure ( 11 , 12 ) and resting-state functional connectivity ( 13 17 ). Specifically, BQ chewers have decreased functional connectivity in the DMN including ventral medial prefrontal cortex (VMPFC), and orbitofrontal cortex (OFC)/anterior cingulate cortex (ACC) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%